MULTIMEDIA INTERAKTIF BERBASIS CANVA UNTUK MENINGKATKAN KEMAMPUAN KETERAMPILAN MENULIS PUISI SISWA KELAS IV SEKOLAH DASAR - Al Furqon, Muhammad; Arita Marini; Gusti Yarmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the benefits of interactive digital learning media in the form of Canva to improve the poetry writing skills of Grade IV elementary school students. Learning media is an important part of the teaching and learning process. Canva is one of the interactive learning media tools that can enhance poetry reading skills in Grade IV students. This research uses a descriptive qualitative method with a literature study technique. The data collection technique used is literature review, conducted by searching for relevant and appropriate scientific articles related to the research topic. A total of 7 articles were cited, sourced from accredited journals such as SINTA and Garuda, within the last 5 years (2020–2025).